1989
DOI: 10.1177/101053958900300106
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Japanese and British BCG Vaccine Strains in Newborn Infants

Abstract: A prospective study on the British and Japanese BCG vaccines in newborn infants was carried out in which 317 and 285 infants were randomly allocated and vaccinated with the British and Japanese BCG vaccines, respectively. Four follow-up examinations were carried out with an average of 98% of the study cohort attending all sessions. About half the infants did not produce any visible response at the end of the first week. All, by the end of the third month, had characteristic BCG scars with an average diameter o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Breast-fed Canadian-Cree infants showed significant enhanced cell-mediated immunity after bacillus Calmette-Guérin (BCG) immunization at birth but not at 1 month of age. 92 However, Goh et al 93 tested Japanese and British BCG vaccines and noticed that after statistical adjustment, breast-feeding practices did not influence infants' immunologic response. For live virus vaccines (MMR), breast-feeding significantly increased cell-mediated immunity in MMR-vaccinated Canadian Cree children.…”
Section: Parenteral Vaccinesmentioning
confidence: 99%
“…Breast-fed Canadian-Cree infants showed significant enhanced cell-mediated immunity after bacillus Calmette-Guérin (BCG) immunization at birth but not at 1 month of age. 92 However, Goh et al 93 tested Japanese and British BCG vaccines and noticed that after statistical adjustment, breast-feeding practices did not influence infants' immunologic response. For live virus vaccines (MMR), breast-feeding significantly increased cell-mediated immunity in MMR-vaccinated Canadian Cree children.…”
Section: Parenteral Vaccinesmentioning
confidence: 99%
“…For instance, studies have reported enhanced, decreased, or no difference in the immune response to some vaccinations, comparing breastfed to non-breastfed infants ( Dórea 2012 ). For BCG vaccines specifically, one study observed that breastfeeding enhanced lymphocyte blastogenesis (stimulated by purified protein derivative of Mycobacterium tuberculosis ) ( Pabst et al 1989 ), and a second study, that examined Mantoux test results at 6 months, found no difference in tuberculin response size across different strata of breastfeeding duration ( Goh et al 1989 ). Whether breastfeeding is a true confounder or a proxy of exposure that drives its inverse association with anti-BCG antibody levels is difficult to determine.…”
Section: Discussionmentioning
confidence: 99%